TGF-β Signaling Promotes Glioma Progression Through Stabilizing Sox9 - Chao, Min; Liu, Nan; Sun, Zhichuan; Jiang, Yongli; Jiang, Tongtong; Xv, Meng; Jia, Lintao; Tu, Yanyang; Wang, Liang (Frontiers in Immunology, 2021)
Gliomas are brain and spinal cord malignancies characterized by high malignancy, high recurrence and poor prognosis, the underlying mechanisms of which remain largely elusive. Here, we found that the Sry-related high mobility group box (Sox) family transcription factor, Sox9, was upregulated and correlated with poor prognosis of clinical gliomas. Sox9 promotes migration and invasion of glioma cells and in vivo development of xenograft tumors from inoculated glioma cells. Sox9 functions downstream of the transforming growth factor-β (TGF-β) pathway, in which TGF-β signaling prevent proteasomal degradation of the Sox9 protein in glioma cells. These findings provide novel insight into the wide interplay between TGF-β signaling and oncogenic transcription factors, and have implications for targeted therapy and prognostic assessment of gliomas.